A method for monitoring solar diffuser's bidirectional reflectance distribution function degradation in geostationary orbit. Issue 1 (1st January 2020) - Wang, Wei; Zhang, Li-Ming; Xu, Weiwei; Si, Xiao-Long; Huang, Wen-Xin
ABSTRACT: The advanced geosynchronous radiation imager (AGRI) is a geostationary sensor whose reflective solar band is calibrated by a solar diffuser (SD). The SD bidirectional reflectance distribution function (BRDF) degrades over time in the space environment. This degradation can be measured through the SD reflectance degradation monitor (SDRDM). The SDRDM calibration data are normally collected by three filtered detectors, covering wavelengths from 0.45μm to 0.90μm. The SD reflectance degradation can be derived by trending the ratio of the background-subtracted solar-angle corrected SDRDM sun and SD view responses. The conventional monitoring methods rely on geometry factors of the sun view port and the relative BRDF of the SD, and these parameters can cause uncertainties. Aiming at these uncertain factors, the present study collects calibration data at the same solar angle. This method compares the detector digital counts obtained at different times but with the same solar angle. Consequently, it cancels out the angle-dependent parameter to obtain the ratio of the BRDF degradation factors. The obtained results show that monitoring uncertainty of the proposed method is less than 0.18%, while the corresponding monitoring error is less than 0.66%. This method can be applicated in SD's BRDF monitoring.